Tantra : sex, secrecy politics, and power in the study of religions - Urban, Hugh B. (University of California Press, 2003)
Tantra seemingly combines sexuality, sensual pleasure, and the full range of physical experience with the religious life and has proven a key factor in the imagining of India. This book offers a critical account of how the phenomenon has come to be.